ASSESSMENT OF MEAN DISTANCE BETWEEN CENTRAL INCISOR AND INCISIVE PAPILLA WITH RESPECT TO STANDARDIZED ARCH FORM IN DENTATE SUBJECTS - Ussamah Waheed Jatala; Anam Fayyaz Bashir; Nazia Yazdanie (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Edentulous patients require accurate positioning of artificial maxillary anterior teeth in complete dentures to recover the esthetic and phonetic characteristics. This positioning is guided by measuring distance between central incisor (CI) and incisive papilla (IP) in dentate subjects which varies according to the ovoid, square and tapered maxillary arch forms.Objectives: 1- To determine the frequency of three different arch forms in dentate patients;2- To assess the mean distance between central incisor and incisive papilla in each of the three maxillary arch forms.METHODOLOGY: 130 cases were selected by non-probability consecutive sampling, which included both genders and age range of 20-40 years. Impressions of maxillary arches were recorded and their casts photocopied. Arch form template was used to standardize the assessment of arch forms by best-fit method on the photocopies. The distance between mesio-incisal edge of CI and posterior border of IP was measured with digital verniercalipers (SparkFun,Colorado).RESULTS: Out of 130 subjects, 54 males and 76 females were present. The ovoid arch form was the most frequent form recorded at 67% (n=87) while the tapered arch was the least at 14% (n=18). The overall mean distance between central incisor (CI) and incisive papilla (IP) was 11.34mm (7.58mm - 16.45mm). The mean distance was the highest for ovoid arch form (11.58mm) and lowest for square (10.49) with a statistically significant difference (p=0.016) between the two arch forms.CONCLUSION: The ovoid arch was the most frequent arch form found in dentate subjects. The mean distance recorded was highest for ovoid arch followed by tapering arch and least for square arches.